9-19-08LectPHY2048

# 9-19-08LectPHY2048 - More applications of Newtons second...

This preview shows pages 1–7. Sign up to view the full content.

F T –T θ m 2 m 1 || 1 m gsin −θ θ m 1 g m 2 g Last class we solved a problem in which we effectively bent our coordinate axis (at a pulley) to describe the motion of the two sides of the system. || More applications of Newton’s second law

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
We now bend the coordinate system 180 o to solve the dynamics of what is called Atwood’s Machine. m 1 m 2 massless pulley, rope For the circumstance to the right suppose m 2 > m 1 . We chose this “direction” of acceleration as being positive . When the masses are released m 2 will accelerate downwards, while m 1 will accelerate upwards. a a Direction is in quotes because this means that acceleration upwards on the left is positive , but acceleration downwards on the right is positive. This is required by the constraint of the rope that dictates that the when one accelerates up the other accelerates down.
m 1 m 2 T –T m 2 g –m 1 g Having chosen the signs of the of acceleration on the two sides also fixes the signs of the forces on the two sides. On the left we have the tension, T , from the rope acting upward as positive and the force of gravity acting downward coming in as negative: –m 1 g (as usual). On the right, however, since acceleration downward is positive, forces downward are positive while those upward are negative. So there we have –T for the upward tension in the rope and +m 2 g .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
21 11 (m m ) Tm g m g −= + And using this in the expression for m 1 allows solving for T , 12 2m m Tg = + Adding the equations eliminates T 2112 mg mg ma ma =+ m )g m )a ag = + For m 1 : 1 FT m g m a = For, m 2 : 22 2 m g m a = −+ = With these definitions Newton’s 2 nd law becomes: m 1 m 2 T –T m 2 g –m 1 g
21 (m m ) ag = + 12 2m m Tg = + m 1 m 2 T –T m 2 g –m 1 g , Do these make sense? i.e. m 2 accelerates down with a = g. If instead m 2 = 0 , a = – g , i.e. m 1 accelerates down at the right rate & T = 0 . Good. If m 1 = m 2 = m, a = 0 , and T = mg . Also good . If m 1 = 0 , the first eqn. gives, 2 2 0) g == + While the second eqn gives, for m 1 = 0 , T = 0. Both of which would be expected .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
21 (m m ) ag = + m 1 m 2 T –T m 2 g –m 1 g Notice that the acceleration of the two masses is the acceleration of gravity, g, times the difference in the masses divided by their sum.
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 23

9-19-08LectPHY2048 - More applications of Newtons second...

This preview shows document pages 1 - 7. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online